THE ACCEPTANCE OF E-LEARNING IN TVET EDUCATION: A CASE STUDY OF CULINARY ARTS STUDENTS - Noor Atika binti Mazlan; Wan Rusni binti Wan Ismail; Noraini binti Rahim; Nor Hafizah binti Mazlan (Journal of Islamic, Social, Economics and Development, 2022)
The COVID-19 epidemic gives a huge impact on educational sectors across theworld. Due to Movement Control Order (MCO), all classes were advised to be executed throughe-learning or open and distance learning (ODL) since students and lecturers were physicallyseparated and a face-to-face connection was difficult. It is quite challenging to adopt e-learningfor TVET or laboratory courses. Hence, this research aims to investigate the relationshipbetween perceived usefulness, perceived ease of use, perceived self-efficacy, and intention touse an e-learning by using the structural model based on the Technology Acceptance Model(TAM). 140 respondents consisted of students from UiTM Permatang Pauh campus whoenrolled in culinary art courses participate in this survey. Pearson correlation was used tomeasure the relationship between the variables. The results show a significant relationshipbetween all the independent variables which are perceived usefulness, perceived ease of use,perceived self-efficacy with the dependent variable which is an intention to use e-learning. Thestudy's findings would be valuable to the university, particularly to UiTM Hospitality andTourism faculty and associated department, in terms of improving and maintaining the system,as well as ensuring that it is fully utilized as an educational platform by students and educators